2011
DOI: 10.2310/7750.2011.10078
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate-Induced Cutaneous Ulcers in a Nonpsoriatic Patient: Case Report and Review of the Literature

Abstract: We report the fifth case of methotrexate-induced cutaneous ulceration in a nonpsoriatic patient and review the literature on this unusual drug reaction. Methotrexate can induce cutaneous ulceration in nonpsoriatic patients and should be considered a potential cause of ulceration in patients treated with this antimitotic agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 8 publications
1
16
0
2
Order By: Relevance
“…These ulcerations are painful, and it has recently been suggested that they are more frequent on acral areas [15]. Skin ulceration has also been described in patients with mycosis fungoides receiving MTX [16,17] as well as in patients without skin lesions receiving MTX [18,19,20]. In the latter the exact mechanism of ulceration has not been elucidated, but direct toxicity associated with local factors has been suggested [19].…”
Section: Discussionmentioning
confidence: 99%
“…These ulcerations are painful, and it has recently been suggested that they are more frequent on acral areas [15]. Skin ulceration has also been described in patients with mycosis fungoides receiving MTX [16,17] as well as in patients without skin lesions receiving MTX [18,19,20]. In the latter the exact mechanism of ulceration has not been elucidated, but direct toxicity associated with local factors has been suggested [19].…”
Section: Discussionmentioning
confidence: 99%
“…One week after MTX discontinuation the skin lesions had resolved ( D−F ). MTX‐induced erosions in patients without a history of psoriasis are rare . Reported predisposing factors include initiation/increase or restarting MTX treatment, renal impairment, NSAID intake, age >55 years, folate deficiency, low serum albumin level, and drug interactions (e.g.…”
mentioning
confidence: 99%
“…He had not undergone any changes in dosage, nor was he resuming treatment after a drug hiatus, both of which may precipitate MTX toxicity . Compared with previous reports of toxicity, which occurred at 15 mg/week to 5 mg/day, we suggest that his remarkable susceptibility was due to decreased renal clearance …”
Section: Discussionmentioning
confidence: 99%
“…Previous cases of MTX‐induced skin necrosis in patients without psoriasis have described ulcerations affecting the oral, acral and extensor surfaces . Rapid proliferation of the oral mucosa or increased epithelial thickness with high mitotic indices at the acral or extensor surfaces may explain the increased susceptibility to MTX at these sites .…”
Section: Discussionmentioning
confidence: 99%